The Effect of Direct Communication between Emergency Physicians and Interventional Cardiologists on Door to Balloon Times in STEMI - Kwak, Min-Ji; Kim, Kyuseok; Rhee, Joong Eui; Shin, Jung Ho; Suh, Gil Joon; Jo, Young-Seok; Youn, Tae-Jin; Chung, Woo-Young; Chae, In-Ho; Choi, Dong-Ju; Lee, Christopher C.; Singer, Adam J. (Journal of Korean medical science, 2008)
We developed an institutional protocol mandating emergency physicians to contact the interventional cardiologist directly in all cases of ST-segment elevation myocardial infarction (STEMI) and hypothesized that this would reduce door-to-balloon-times (DTBT). From January 2004 to July 2006, 208 patients with STEMI were treated with primary percutaneous coronary intervention (PCI). A total of 144 patients were treated before implementing the new protocol ("before") and 64 patients were treated after the implementation ("after"). The DTBT was significantly reduced from 148+/-101 min to 108+/-56 min (p<0.05). While only 25% of the "before'' patients received PCI within 90 min after arrival, 50% of the "after'' patients received PCI within 90 min (p<0.05). There were no significant differences between two groups in other outcomes (postprocedural TIMI flow, mortality, subsequent stroke, heart failure, shock, reinfarction, length of stay in intensive care unit, and the total hospital length of stay). In conclusion, mandating emergency physicians to directly notify interventional cardiologists of all STEMI patients reduces DTBT.